Pengaruh Pemberian Makanan Pendamping Asi ( MP – ASI) Dini Terhadap Kejadian Kekurangan Energi Protein (KEP) Pada Anak Umur 0 – 24 Bulan Di Wilayah Kota Kediri - Ira Titisari; Susanti Pratamaningtyas; Eny Sendra (coba, 2014)
Should we know that Mother’s Milk Complementary Foods is begin giving when someday after the baby was born. This is deficient think, because Mother’s Milk Complementary Foods present can make malnutrition consist or disturb child development (Energy-Protein Malnutrition). The destination of this research is to find out effect of giving too early Mother’s Milk complementary Foods with Energy-Protein Malnutrition incident to children on zero until twenty four months old. The methode of this research is the corelation with analitic case control characteristic that is eight child as case and eight others as control of fill up inclusion criteria . The samples will take by purposive sampling tehnis . The finishing data collection are using questionaire by weight and height measurement. The data analitic are using fisher exact probability test with 5% significancy. The result of this research is giving Mother’s Milk Complementary Foods to 87,5% Energy-Protein Malnutrition group and 25% non Energy-Protein Malnutrition is not timely. 100% Energy-Protein Malnutrition is nasty. There is an effect of giving too early Mother’s Food Complementary Foods in Energy-Protein Malnutrition accident on children at zero untill six months old. Be expected for the health personnel to give information and counseling about to give too early Mother’s Milk Complementary Foods about effect and the interval, at the same time for a children whio has Energy-Protein Malnutrition must give supplementary food that appropriate with the local program and integrated by Department of health. Keywords = Giving too early Mother’s Milk Complementary Foods, Energy-Protein Malnutrition